1999
DOI: 10.1002/chin.199948135
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Triazenopyrazole Derivatives as Potential Inhibitors of HIV‐1.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Chemical reactions, such as pyrazole synthesis reactions and Schiff base reactions, that can proceed rapidly and can be simultaneously detected by UASI‐MS were selected as the model reactions. Pyrazole and its derivatives have been used as antiviral, anti‐tumor, and antidepressant medicines. Usually, several tens of minutes are required to complete a pyrazole reaction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical reactions, such as pyrazole synthesis reactions and Schiff base reactions, that can proceed rapidly and can be simultaneously detected by UASI‐MS were selected as the model reactions. Pyrazole and its derivatives have been used as antiviral, anti‐tumor, and antidepressant medicines. Usually, several tens of minutes are required to complete a pyrazole reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole and its derivatives have been used as antiviral, 28 antitumor, 29 and antidepressant 30 medicines. Usually, several tens of minutes are required to complete a pyrazole reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of the naturally occurring C-glycoside antibiotic pyrazofurin; 4-hydroxy-3-b-Dribofuranosyl-1H-pyrazole-5-carboxamide 6 , however, has provided a basis for a rational design of new pyrazoles as potential antimicrobial 7,8 , antiviral 9,10 and anticancer agents 8,[11][12][13] . It has also been reported that isoquinoline-1-carboxaldehyde thiosemicarbazone and its several congeners which possess the N-N-S or O-N-S tridentate ligand system, exhibit substantial antineoplastic activity 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole derivatives are well recognised for their biological activities as potential HIV-1 inhibitors, antiviral, anticancer agents, insecticides and fungicides. [1][2][3][4] Pyrazole fused-heterocycles, namely pyrazolo [4,3-d]pyrimidine derivatives are also of great interest as potential biologically active molecules. Several members of this class exhibit recognised pharmacological activities for treatment of thromboembolic disorders, with affinity at adenosine receptors for the treatment of bronchoconstriction and cardiac insufficiency, as well as Hsp90 inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%